2019
DOI: 10.3389/fimmu.2018.03069
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to the Dual Threat of Silica Exposure and Mycobacterium tuberculosis

Abstract: Exposure to silica and the consequent development of silicosis are well-known health problems in countries with mining and other dust producing industries. Apart from its direct fibrotic effect on lung tissue, chronic and immunomodulatory character of silica causes susceptibility to tuberculosis (TB) leading to a significantly higher TB incidence in silica-exposed populations. The presence of silica particles in the lung and silicosis may facilitate initiation of tuberculous infection and progression to active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 144 publications
3
34
0
Order By: Relevance
“…In rat models, defence against Mycobacterium tuberculosis becomes poorer as silicosis progresses [25] . However, silica-induced Th1 responses, with TNF-alpha and IFN-gamma production, should contribute to resistance to, or elimination of, Mycobacterium tuberculosis [26] . The pathophysiological mechanisms are still incompletely identified.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In rat models, defence against Mycobacterium tuberculosis becomes poorer as silicosis progresses [25] . However, silica-induced Th1 responses, with TNF-alpha and IFN-gamma production, should contribute to resistance to, or elimination of, Mycobacterium tuberculosis [26] . The pathophysiological mechanisms are still incompletely identified.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Additional studies are clearly needed on the pathophysiology of silico-tuberculosis. In particular, no research has been done on dendritic cells, neutrophils, NK cells, B cells, and only scanted and contradictory data are available on T cells [26] .…”
Section: Main Research Needsmentioning
confidence: 99%
“…Fine particulate air pollutants have been associated with tuberculosis incidence and outcome (Popovic et al, 2019). However, the underlying mechanisms by which patients exposed to silica become predisposed to the development of severe tuberculosis are poorly understood (Kone cný et al, 2019). Inhaled crystalline silica affects immune and non-immune cell types, resulting in responses ranging from inflammation to oxidative stress and cell death (Joshi and Knecht, 2013;Porter et al, 2004Porter et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that patients with TB/silicosis had slower M. tuberculosis elimination rates by TB-MBLA compared to those with TB and without silicosis. This slow rate of elimination could partially be attributed to the underlying pulmonary pathophysiology which can include progressive massive fibrosis [28,29] , and anatomically, a blunted local host immune response to M. tuberculosis infection [28] . We observed a similarly slower rate of M. tuberculosis elimination among patients with RR/MDR-TB who had high initial bacterial load, which supplements previous studies of TB-MBLA kinetics from patients with drug sensitive TB [6,8,19] .…”
Section: This Observation Concurs With Previous Reports That the Bactmentioning
confidence: 99%